Determinants of instant messenger (IM) adoption and its effect on team performance: mediating role of knowledge creation and quality communication - Tarofder, Arun Kumar; Haque, A. K. M. Ahasanul; Nawaz, Nishad; Raisal, Ismail; Musah, Adiza Alhassan; M. D. Kassim, Aza Azlina (Public Library of Science, 2023)
Computer-mediated communication has dramatically transformed the human communication landscape by enhancing speed, content and social presence. The world has been experiencing a sharp decline in using email and phone calls due to organizations’ rapid adoption of instant messenger (IM) for their day-to-day communication with their stakeholders. Moreover, the world has been experiencing a sharp decline in using email and phone calls since the beginning of the IM era. Hence, the aim of this study is to comprehend the IM adoption process through the lens of three theories. A structured questionnaire was developed to collect data from the organizations and test hypotheses using consistent PLS-SEM (PLSc) in SMART PLS combined with bootstrapping. The results indicated that parallelism is the most dominating factor explaining IM adoption in organizations followed by transmission velocity, rehearsability and symbol set. The findings of this study also confirmed that team performance is not influenced by communication but by the quality of the communication and the level of knowledge within the group that can create using instant messenger. Indeed, this empirical study is one of the limited investigations that combine three theories to explain the IM adoption process and its effect on team performance. Moreover, this study contributes both theoretically and practically to comprehending the adoption process of IM. Lastly, this study reconfirmed the importance of Media Synchronicity Theory (MST) and Social Presence Theory (SPT) in predicting IM adoption; and the findings of this research extended the applications of the Adaptive Structuration Theory (AST) from the IM perspective, which is, indeed, rare. Finally, this study provides a great foundation for managers to understand the importance of IM in their day-to-day communication systems.